Fingerprinting using vibrational spectroscopy and chemometrics for determining the presence of non-halal meats in food products - Claude Mona Airin; Muhammad Jefriyanto Budikafa; Yuny Erwanto; Sudjadi Sudjadi; Pudji Astuti; Sarmin Sarmin; Anjar Windarsih; Abdul Rohman (Applied Food Research)
The development of analytical methods designed to detect non-halal meats in the presence of halal meats has increased exponentially in the last 20 years. High quality meats are substituted with lesser ones that are non-halal meats. This issue of particular concern for the Islamic community since Muslims are not allowed to consume any food products containing non-halal meats such as pork, rat meat, and canine meat. Most tests are qualitative although quantitative methods are also available. Near infrared spectroscopy (NIR-S) and Fourier transform infrared spectroscopy (FTIR-S) in combination with chemometrics offers the potential tools for the qualitative or quantitative analyses of non-halal meats in food products. The objective of this review was to highlight the recent applications of NIR-S and FTIR-S coupled with chemometrics, especially pattern recognition and multivariate calibrations for determination of non-halal meats in food samples. This review, hopefully will be useful to regulatory bodies responsible for halal certification.